2020
DOI: 10.1093/humrep/dez288
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in age at menarche and age at menopause: a population study of 312 656 women in Norway

Abstract: STUDY QUESTION Have mean age at menarche or mean age at natural menopause changed from the 1939 birth cohort to the 1964 birth cohort? SUMMARY ANSWER We estimated a minor decrease in mean age at menarche and an increase by nearly 3 years in mean age at natural menopause. WHAT IS KNOWN ALREADY In the Western world, age at menarche decreased across birth cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 54 publications
2
43
1
2
Order By: Relevance
“…The age at menarche declined between the 19th century and the first half of the 20th century in Western countries (57)(58)(59)(60). In Norway, the menarcheal age fell from above 15.6 years for women born around 1850 to about 13.3 years for women born after 1940 (58) and has been stable at around 13 years since then (61)(62)(63)(64)(65)(66). This finding is consistent with trends in other European countries (27,30,31,67).…”
Section: Historical Trends In the Timing Of Menarchesupporting
confidence: 84%
See 2 more Smart Citations
“…The age at menarche declined between the 19th century and the first half of the 20th century in Western countries (57)(58)(59)(60). In Norway, the menarcheal age fell from above 15.6 years for women born around 1850 to about 13.3 years for women born after 1940 (58) and has been stable at around 13 years since then (61)(62)(63)(64)(65)(66). This finding is consistent with trends in other European countries (27,30,31,67).…”
Section: Historical Trends In the Timing Of Menarchesupporting
confidence: 84%
“…Compared to the current pubertal references used in Norway based on Danish data from 1991-1993, our estimated ages at onset for breast (B2) and pubic hair development (PH2) and menarche were advanced by 0.5, 0.4 and 0.7 years (27), respectively ( Table 5). The Tanner B3 and B4 stages occurred 0.9 and 0.8 years earlier (27) (66). When reviewing the published ages at menarche in Norway, our estimate for girls with a known Norwegian origin (mean age: 13.1 years) was still in the lower range compared to previous estimates ( Figure 5).…”
Section: Pubertal References Compared To Current Referencesmentioning
confidence: 51%
See 1 more Smart Citation
“…In general, the cohort is taken to be premenopausal from population statistics. 47 Longer term repeatability will also reflect the instability of scanner performance, as well as changes arising from hardware or software. In this study, the effect of specific acquisition parameters on repeatability was not considered, but the chosen protocol is a realistic reflection of clinical DWI protocols and so presents a fair indication of expected CoVs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a population study of 312,656 women born in Norway between 1936 and 1964 has found that their mean age at natural menopause did indeed increase – by more than two years over the study period, rising from 50.31 years in those born during 1936–1939 to 52.73 years in those born during 1960–1964. 3…”
Section: Age At Menopause and The Risk Of Chronic Illnessmentioning
confidence: 99%